Inventory of the Citrus in Barimbun Village, Tabalong District - Masriana, Siti; Halang, Bunda; Mahrudin, Mahrudin (Journal Of Biology Education Research (JBER), 2023)
Indonesia is rich in flora diversity, especially fruit plants. One of fruit plants that is familiar to Indonesian people is the orange tree. Orange trees are annual plants originating from the Asian continent, especially India to China. In Indonesia, orange plants are diverse and have unique characteristics in the form of aroma, color and taste that are different from other fruits. The aim of this research is to describe the diversity of citrus plants (genus Citrus) in Barimbun Village, Tabalong. This research uses the line transect method. The research results found 7 types of oranges, namely, Citrus microcarpa, Citrus jambhiri, Citrus aurantifolia, Citrus gandis, Citrus hystrix, Citrus sinensis, and Citrus limon. Moreover, the abiotic factors give good value which means a suitable habitat for oranges. From this study, it may conclude that Barimbun Village, Tabalong District is a suitable habitat for orange plant because this area has enough amount of rainfall and stabil temperature.